2001
DOI: 10.1002/jpp.338
|View full text |Cite
|
Sign up to set email alerts
|

The axial coordination in subphthalocyanines: Geometrical and electronic aspects

Abstract: Theoretical calculations were performed for studying the electronic molecular structure of axial subphthalocyanine (SubPc) derivatives. The intermolecular SubPc interactions were also investigated at theoretical level using adequate models. These models represent the interaction of one Cl(OR)-SubPc with the surrounding molecules through the Cl atom as well as the interaction of the Cl-SubPc with an incoming diiminoisoindole group in the first steps of the open ring reaction. The SubPc complexes with more elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 28 publications
5
36
0
Order By: Relevance
“…This demonstrates that, in our case, the electron-withdrawing process is mostly inductive in nature since theoretical and experimental studies have shown that the B-Cl distance is correlated to the electron donor/acceptor properties of the peripheral substituents. 35 The most significant structural difference among the series lies, not surprisingly, in the relative orientation of the nitro group with respect to the plane of the adjacent phenyl ring. 36, 37 In the meta isomers 1 and 2 the nitro groups are coplanar to the phenyl ring whereas in the ortho isomers 3 and 4 the nitro groups are twisted ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demonstrates that, in our case, the electron-withdrawing process is mostly inductive in nature since theoretical and experimental studies have shown that the B-Cl distance is correlated to the electron donor/acceptor properties of the peripheral substituents. 35 The most significant structural difference among the series lies, not surprisingly, in the relative orientation of the nitro group with respect to the plane of the adjacent phenyl ring. 36, 37 In the meta isomers 1 and 2 the nitro groups are coplanar to the phenyl ring whereas in the ortho isomers 3 and 4 the nitro groups are twisted ca.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously demonstrated that, likewise, they do not depend on the nature of both the peripheral and the axial substituents. 35 Thus, it may be considered as a geometrical constant that characterizes the rigid core of the subphthalocyanines. Also, it is interesting to note that the B-Cl bond distance remains invariable for all the studied compounds (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation and reduction give rise to the lengthening and shortening, respectively, of the BCl bond length. A possible broad explanation for this fact is that the addition of one or more electrons increases the electron density in the macrocycle (because the redox processes in SubPc mainly involve the macrocycle but not the Cl axial substituent 19–21) and, consequently, leads to an increase of the repulsion between the Cl atom and the macrocycle that are both negatively charged. Because Δ d (+1→+2)BCl/Δ d (0→+1)BCl and Δ d (+1→+2)BCl/Δ d (0→+1)BCl are less than 2, it can be concluded that these repulsive effects are not additive.…”
Section: Resultsmentioning
confidence: 99%
“…This may be explained taking into account that the reductive electrons are mostly located in the macrocycle as suggested by the spatial distribution of the LUMOs (see Refs. 19–21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation